PENINGKATKAN HASIL BELAJAR GEOGRAFI MATERI DASARDASAR PEMETAAN DENGAN MODEL BELAJAR THINK-PAIRSHARE (TPS) PADA PESERTA DIDIK KELAS X SMA NEGERI 2 MAUMERE - EMIRENSIANA DUA NURAK BELA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This class action research was conducted to uncover the application of cooperative learning with Think-Pair-Share models for student learning outcomes on the subject of geography mapping basics. This type of research is action research conducted in 2 cycles. Each cycle consists of four stages: planning, acting and observing, reflecting, and refitting. The subjects of this study were Class X IS4 students of SMA Negeri 2 Maumere. Data obtained in the form of test results and non-test results. The results showed that the learning outcomes of students increased from cycle I to cycle II which was 76.00% in cycle I to 88.00% in cycle II. This class action research concludes that 1. Cooperative learning with the Think-Pair-Share model can improve student learning outcomes in geographic subjects based on mapping the material by proven to increase participants’ mastery of learning to reach 88% in the cycle. 2. Think-Pair-Share learning model in this study is proven to be able to increase learning activities.